PEMBUATAN DAFTAR ASET TETAP DAN MENGHITUNG BEBAN PENYUSUTAN PADA SD IT LUHURING BUDI KELURAHAN AGROWISATA KECAMATAN RUMBAI BARAT - Salmiah, Neneng; Wiyati, Rita; Wibisono, Rafidianto; Februari, Aura Cinta (Komunitas Manajemen Kompetitif, 2025)
Fixed assets are one of the assets owned by entities including the Luhuring Budi Integrated Islamic Elementary School (SD IT). Fixed assets are presented in the Statement of Financial Position as the acquisition price consists of land, school buildings, equipment and vehicles. Fixed assets have a limited useful life except for land, so fixed assets other than land must be depreciated and recorded as depreciation expenses. The depreciation expense is presented in the Income Statement as a deduction of income. This Community Service (PKM) is a continuation of the previous PKM, namely the financial recording of SD IT Luhuring Budi where after recording the purchase of fixed assets should be followed by making a list of fixed assets. However, from the previous PKM activities, information was obtained that SD IT Luhuring Budi had not made a list of fixed assets and did not have a depreciation expense account. This is because the Bookkeeping Section and Treasurer of SD IT Luhuring Budi do not have knowledge about making a list of fixed assets and calculating depreciation expenses. Therefore, the PKM Team of FEB Unilak Lecturers is motivated to carry out advanced PKM to provide knowledge about making a list of fixed assets and calculating depreciation expenses to the Bookkeeping Section and Treasurer of SD IT Luhuring Budi. The methods used are conducting pre-tests, material submissions, training, questions and answers, and post tests. The results achieved from this PKM activity were obtained from the comparison of post test results with pre-test results. The results of the comparison of the post test with the pre-test showed that before the PKM, most of the participants, namely the Treasurer, Operational and Bookkeeping Section, Education Personnel and several teachers of SD IT Luhuring Budi did not have the knowledge and skills to make a list of fixed assets and calculate depreciation expenses using Microsoft Excel. After the PKM, there is an increase in knowledge and skills in listing fixed assets and calculating depreciation expenses using Microsoft Excel.